Trends in functional programming : 18th International Symposium, TFP 2017, Canterbury, UK, June 19-21, 2017, revised selected papers /: 18th International Symposium, TFP 2017, Canterbury, UK, June 19-21, 2017, revised selected papers. (2018) - Unknown
No abstract available